Clinical Efficacy of Diphenylcyclopropenone Immunotherapy as Monotherapy for Multiple Viral Warts. Issue 3 (May 2018) - Park, Jun Yeong; Park, Bok Won; Cho, Eun Byul; Park, Eun Joo; Kim, Kwang Ho; Kim, Kwang Joong
Background: Diphenylcyclopropenone (DPCP) immunotherapy for viral warts has been used for many years, but no studies have analyzed the treatment effects of DPCP alone, without the use of conventional therapy before immunotherapy. Objectives: We evaluated clinical efficacy of DPCP monotherapy compared to cryotherapy and pulsed dye laser (PDL) therapy. We also assessed the impact of initial sensitization on clinical response. Methods: We retrospectively analyzed the medical records of 250 patients with multiple viral warts between January 2008 and December 2015. Results: The DPCP-only group (n = 43) showed a lower clinical response (75.6%) than the cryotherapy-only group (n = 171, 89.8%, P < .01) and PDL-only group (n = 36, 90.3%, P < .01). The positive clinical response was 76.3% (119/156) in the successful sensitization group (n = 21) and 74.4% in the failed sensitization group ( P = .870). Conclusions: DPCP monotherapy has a lower clinical response than conventional therapy. Initial sensitization to DPCP does not predict a failed response with continued immunotherapy for viral warts.